Analytical study on in-plane free vibration of a cable network with straight alignment rigid cross-ties. (May 2015) - Ahmad, Javaid; Cheng, Shaohong
Using cross-ties is one of the effective countermeasures to suppress unfavorable bridge stay cable vibrations. It has been successfully applied in the field. However, dynamic behavior of cable networks is still not clearly understood, which hinders the development of a more efficient design. The current paper aims at extending the existing analytical studies on in-plane free vibration of cable networks by developing closed-form modal solutions for a wider series of cases, in particular for general cable networks consisting of n horizontally laid main cables interconnected transversely with a single line of rigid cross-ties. The validity of these analytical modal solutions is verified by independent finite element simulations. These closed-form modal solutions offer a clear elucidation of the mechanics underlying various modal behaviors observed in cable networks of different layout and structural properties. In addition, based on the proposed analytical formulation, the important system parameters of cable networks are identified. The unique features associated with cable networks of a number of specific configurations are investigated and discussed.